2021
DOI: 10.1029/2021wr031026
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn From the Water Retention Characteristic of a Soil Regarding Its Hydrological and Agricultural Functions? Review and Analysis of Actual Knowledge

Abstract: The soil properties of the upper soil layer determine the partitioning between infiltration, runoff, and evaporation, key processes related to soil agricultural and hydrological functioning. It is therefore important to have some information on these soil functions based on available and easy‐to‐measure properties. This study presents what we can learn a‐priori from the soil water retention characteristic (WRC) on some important hydrological and agricultural functions. Based on a mathematical expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 84 publications
(175 reference statements)
0
12
0
Order By: Relevance
“…The hysteresis phenomenon found in the relationships between the two plant water potentials: Ψ trunk vs. Ψ stem ( Figure 8A ), which was more noticeable for Ψ trunk vs. Ψ leaf ( Figure 8B ), was higher for the highest imposed soil water deficit (α=100%). This hysteretic behaviour revealed that the water status of the trunk assumes a dominant role in controlling canopy water status as water stress accumulates, which is related to plant hydraulic conductivity during the daily course ( Assouline, 2021 ). In addition, stomata reopened in the afternoon, as indicated by the recovery values of the diurnal pattern of leaf gas exchange ( Figures 9G–I ).…”
Section: Discussionmentioning
confidence: 99%
“…The hysteresis phenomenon found in the relationships between the two plant water potentials: Ψ trunk vs. Ψ stem ( Figure 8A ), which was more noticeable for Ψ trunk vs. Ψ leaf ( Figure 8B ), was higher for the highest imposed soil water deficit (α=100%). This hysteretic behaviour revealed that the water status of the trunk assumes a dominant role in controlling canopy water status as water stress accumulates, which is related to plant hydraulic conductivity during the daily course ( Assouline, 2021 ). In addition, stomata reopened in the afternoon, as indicated by the recovery values of the diurnal pattern of leaf gas exchange ( Figures 9G–I ).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement time is highly variable in each method, and a longer equilibration time is required as h becomes smaller (i.e., more negative). However, there is no single method to characterize a continuous water retention process across the full range of h (Assouline, 2021).…”
Section: Core Ideasmentioning
confidence: 99%
“…Soil water storage (SWS) and availability are two common indicators of soil hydrological function (Assouline, 2021), reflecting the ease of absorbing soil water for crops (Filho et al., 2013; Li et al., 2020). Plant available water (PAW) and least limiting water range (LLWR) are commonly applied to measure the soil water availability for plants from different angles (Asgarzadeh et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil hydrological function is the result of the interaction of multiple soil properties, which makes it hard to analyze the effect of a single soil property on soil hydrological function (Assouline, 2021; Basche & DeLonge, 2017; Bayabil et al., 2019). Previous studies have shown that soil structure plays a vital role in soil hydrological function (Fei et al., 2019; Głąb et al., 2016).…”
Section: Introductionmentioning
confidence: 99%